Safety and immunogenicity of Pfs25H-EPA/Alhydrogel, a transmission-blocking vaccine against Plasmodium falciparum: a randomised, double-blind, comparator-controlled, dose-escalation study in healthy Malian adults. Issue 9 (September 2018) - Sagara, Issaka; Healy, Sara A; Assadou, Mahamadoun H; Gabriel, Erin E; Kone, Mamady; Sissoko, Kourane; Tembine, Intimbeye; Guindo, Merepen A; Doucoure, M'Bouye; Niaré, Karamoko; Dolo, Amagana; Rausch, Kelly M; et al.
Summary: Background: Pfs25H-EPA is a protein-protein conjugate transmission-blocking vaccine against Plasmodium falciparum that is safe and induces functional antibodies in malaria-naive individuals. In this field trial, we assessed Pfs25H-EPA/Alhydrogel for safety and functional immunogenicity in Malian adults. Methods: This double-blind, randomised, comparator-controlled, dose-escalation trial in Bancoumana, Mali, was done in two staggered phases, an initial pilot safety assessment and a subsequent main phase. Healthy village residents aged 18–45 years were eligible if they had normal laboratory results (including HIV, hepatitis B, hepatitis C tests) and had not received a previous malaria vaccine or recent immunosuppressive drugs, vaccines, or blood products. Participants in the pilot safety cohort and the main cohort were assigned (1:1) by block randomisation to a study vaccine group. Participants in the pilot safety cohort received two doses of Pfs25H-EPA/Alhydrogel 16 μg or Euvax B (comparator vaccine), and participants in the main cohort received Pfs25H-EPA/Alhydrogel 47 μg or comparator vaccine (Euvax B for the first, second, and third vaccinations and Menactra for the fourth vaccination). Participants and investigators were masked to group assignment, and randomisation codes in sealed envelopes held by a site pharmacist. Vials with study drug for injection were covered by opaque tape and labelled with a study identification number. Group assignments were unmasked at final study visit. The primary outcomes were safety and tolerability for all vaccinees. The secondary outcome measure was immunogenicity 14 days after vaccination in the per-protocol population, as confirmed by the presence of antibodies against Pfs25H measured by ELISA IgG and antibody functionality assessed by standard membrane feeding assays and by direct skin feeding assays. This trial is registered with ClinicalTrials.gov, number NCT01867463 . Findings: Between May 15, and Jun 16, 2013, 230 individuals were screened for eligibility. 20 individuals were enrolled in the pilot safety cohort; ten participants were assigned to receive Pfs25H-EPA/Alhydrogel 16 μg, and ten participants were assigned to receive comparator vaccine. 100 individuals were enrolled in the main cohort; 50 participants were assigned to receive Pfs25H-EPA/Alhydrogel 47 μg, and 50 participants were assigned to receive comparator vaccine. Compared with comparator vaccinees, Pfs25H vaccinees had more solicited adverse events (137 events vs 86 events; p=0·022) and treatment-related adverse events (191 events vs 126 events, p=0·034), but the number of other adverse events did not differ between study vaccine groups (792 vs 683). Pfs25H antibody titres increased with each dose, with a peak geometric mean of 422·3 ELISA units (95% CI 290–615) after the fourth dose, but decreased relatively rapidly thereafter, with a half-life of 42 days for anti-Pfs25H and 59 days for anti-EPA (median ratio of titres at day 600 to peak, 0·19 for anti-Pfs25H vs 0·29 for anti-EPA; p=0·009). Serum transmission-reducing activity was greater for Pfs25H than for comparator vaccine after the fourth vaccine dose (p<0·001) but not after the third dose (p=0·09). Repeated direct skin feeds were well tolerated, but the number of participants who infected at least one mosquito did not differ between Pfs25H and comparator vaccinees after the fourth dose (p=1, conditional exact). Interpretation: Pfs25H-EPA/Alhydrogel was well tolerated and induced significant serum activity by standard membrane feeding assays but transmission blocking activity was not confirmed by weekly direct skin feed. This activity required four doses, and titres decreased rapidly after the fourth dose. Alternative antigens or combinations should be assessed to improve activity. Funding: Division of Intramural Research, National Institute of Allergy and Infectious Diseases.